Studi Tingkat Keanekaragaman Hayati Lahan Bekas Terbakar di Taman Nasional Sebangau & Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Tumbang Nusa: Study Of Biodiversity Level On Burnt Landa at Sebangau National Park & Forest Area With Spesific Purpose (KHDTK) Tumbang Nusa - Mariaty, Mariaty; Santosa, Purwanto Budi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
The forest and land fires in 2015 caused severe damage to forest areas at Sebangau National Park and KHDTK Tumbang Nusa, where the condition has not to be able to recover as before. This research objective is knowing the effect of forest and land fires on vegetation and the succession process that is happened at TN. Sebangau and KHDTK Tumbang Nusa with methodology field survey and making plots (PU) on the burnt and un-burnt forest for the comparison. Data observation and collection were done appropriately with the vegetation strata, namely the level of seedlings, saplings, poles, and trees. The data analysis used quantitative with calculating the Species Dominance, Species Diversity, Species Richness, and Species Evenness. The research result shows the un-burnt land was observed in TN. Sebangau there are 29 vegetation species, meanwhile the burnt land there are found only rejuvenation level plants, namely Seedlings and Saplings where there are two vegetation species at TN. Sabangau and 4 vegetation species at KHDTK. For species dominance is indicated by a high INP value, the greater value of INP means the forest composition is good enough in terms of density and frequency of species presence. In Sebangau, the highest value of dominance is Tutup Kabali (Diospyros pseudomalabarica) for the tree level, Rambutan Hutan (Nephelium lappaceum) for pole and sapling levels, and Bangkinang (Elaeocarpus glaber Bl) for seedling level, while in KHDTK is Milas/Tumeh (Combretacarpus rotundatus) for the seedling and sapling levels, and Gerunggang (Cratoxylon arborescens) for pole and tree levels. The Analysis Number of species diversity, richness, and evenness species in the two research locations do not show a high value which from data processing result shows the range is low to moderate, nothing high. On burnt land, the succession process happens very slowly because it experienced the severe degradation of land causing the erosion/ subsidence of soil surface so that the forest floor was flooded as the impact of the open canopy and no shade from the bush that dominated.